Non‐binary Encoded Nucleic Acid Barcodes Directly Readable by a Nanopore. (16th March 2022) - Yan, Shuanghong; Wang, Liying; Wang, Yuqin; Cao, Zhenyuan; Zhang, Shanyu; Du, Xiaoyu; Fan, Pingping; Zhang, Panke; Chen, Hong‐Yuan; Huang, Shuo
Abstract: A large collection of unique molecular barcodes is useful in the simultaneous sensing or screening of molecular analytes. Though the sequence of DNA has been widely applied to encode for molecular barcodes, decoding of these barcodes is normally assisted by sequencing. We here demonstrate a barcode system based solely on self‐assembly of synthetic nucleic acids and direct nanopore decoding. Each molecular barcode is composed of " n " distinct information nodes in a non‐binary manner and can be sequentially scanned and decoded by a Mycobacterium smegmatis porin A (MspA) nanopore. Nanopore events containing step‐shaped features were consistently reported. 14 unique information nodes were developed which in principle could encode for 14 n unique molecular barcodes in a barcode containing " n " information nodes. These barcode probes were adapted to detect different antibody proteins or cancer‐related microRNAs, suggesting their immediate application in a wide variety of sensing applications. Abstract : An extremely simple molecular barcoding strategy is proposed based on self‐assembly of synthetic DNA oligomers and direct nanopore decoding. The composition of the barcode probe is highly programmable, and in principle 14 n unique step‐shaped barcode patterns can be generated without nanopore sequencing. Different protein and microRNA targets were identified using this strategy, showing its generality in single molecule sensing.